The magnetic circuit dynamics of a magnetorheological valve with a permanent magnet - Kubík, Michal; Jeniš, Filip (EDP Sciences, 2020)
The magnetorheological (MR) damper uses magnetorheological fluid which, when subjected to magnetic stimuli, generates an increase of damping forces. A significant problem of these dampers is their poor failsafe ability due to power supply interruption. In the case of faults, the damper remains in a low damping state, which is dangerous. This problem can be solved by accommodating a permanent magnet in the magnetic circuit of the damper. However, the magnetic circuit dynamic of this type of damper has rarely been studied. The main aim of this paper is to introduce the magnetic circuit dynamics of the magnetorheological damper/control valve with a permanent magnet. Firstly, the design of the magnetorheological valve with NdFe42 permanent magnet in the magnetic circuit is introduced. The response time of the magnetic field on the unit step of the control signal was calculated by transient magnetic simulation in Ansys Electronics software. The response time of the magnetic field was simulated in the range of 1.2 to 5 ms depending on the electric current magnitude and orientation. The presented MR damper was manufactured and tested. The experiments prove that the permanent magnet significantly affects the dynamics of the magnetic circuit.

The magnetorheological (MR) damper uses magnetorheological fluid which, when subjected to magnetic stimuli, generates an increase of damping forces. A significant problem of these dampers is their poor failsafe ability due to power supply interruption. In the case of faults, the damper remains in a low damping state, which is dangerous. This problem can be solved by accommodating a permanent magnet in the magnetic circuit of the damper. However, the magnetic circuit dynamic of this type of damper has rarely been studied. The main aim of this paper is to introduce the magnetic circuit dynamics of the magnetorheological damper/control valve with a permanent magnet. Firstly, the design of the magnetorheological valve with NdFe42 permanent magnet in the magnetic circuit is introduced. The response time of the magnetic field on the unit step of the control signal was calculated by transient magnetic simulation in Ansys Electronics software. The response time of the magnetic field was simulated in the range of 1.2 to 5 ms depending on the electric current magnitude and orientation. The presented MR damper was manufactured and tested. The experiments prove that the permanent magnet significantly affects the dynamics of the magnetic circuit.
The magnetic circuit dynamics of a magnetorheological valve with a permanent magnet
Keywords: magnetorheological damper; permanent magnet; magnetorheological damper; permanent magnet